Strategi Komunikasi Branding Pemerintah Kota Kupang dalam Mewujudkan Kupang Smart City - Intang Triwulang; Mas’Amah; Frengky Dupe (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the branding communication strategies of the Kupang City Government in realizing Kupang Smart City, evaluate their effectiveness, and identify implementation barriers since its 2019 declaration. Utilizing a qualitative case study approach, data were collected through in-depth interviews, observations, and documentary studies at the Kupang City Communication and Informatics Office. Analysis was conducted using triangulation techniques, supported by theoretical frameworks of communication strategy, corporate strategy, and SWOT analysis. The findings indicate that the branding strategy focuses on digitalization via social media and the promotion of local cultural identity, such as Tenun Bunga Sepe. While effective in building a positive image within the Smart Branding and Smart Economy dimensions, the overall implementation across all six Smart City pillars remains uneven. Primary obstacles include weak inter-agency coordination, budgetary constraints, low digital literacy, and suboptimal infrastructure maintenance. The SWOT evaluation reveals that resource allocation instability and a gap between strategic vision and field execution hinder the formation of a robust brand. The study concludes that the success of Kupang Smart City requires an integrated communication strategy, sustained collective commitment across government departments, and consistent implementation across all pillars.